2021
DOI: 10.1186/s13002-021-00482-9
|View full text |Cite
|
Sign up to set email alerts
|

Preserving for the future the — once widespread but now vanishing — knowledge on traditional pig grazing in forests and marshes (Sava-Bosut floodplain, Serbia)

Abstract: Background Traditional knowledge is key for sustainability, but it is rapidly disappearing. Pig keeping in forests and marshes is an ancient, once widespread, now vanishing practice, with a major economic and ecological potential. The knowledge of pig keepers and the foraging activity of pigs are hardly documented. Methods We studied the knowledge of traditional pig keepers (svinjars) on wild plants and pig foraging on the Sava-Bosut forest-marsh c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
6
1
Order By: Relevance
“…Shrub species such as L. vulgare and E. europaeus, instead, were avoided by pigs in the understory (consumption ≤ 1%), probably because of the presence of toxic compounds (secoiridoid glycosides in L. vulgare and cardenolides in E. europaeus; Wink 2010). Also C. monogyna was avoided by pigs contrary to the findings of Molnár et al (2021), who reported, however, that this species was eaten only when leaves were young and spikes were soft.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Shrub species such as L. vulgare and E. europaeus, instead, were avoided by pigs in the understory (consumption ≤ 1%), probably because of the presence of toxic compounds (secoiridoid glycosides in L. vulgare and cardenolides in E. europaeus; Wink 2010). Also C. monogyna was avoided by pigs contrary to the findings of Molnár et al (2021), who reported, however, that this species was eaten only when leaves were young and spikes were soft.…”
Section: Discussioncontrasting
confidence: 81%
“…Poisoning by R. pseudoacacia was documented in other livestock species, such as horses (Vanschandevijl et al 2010), whereas goats are able to forage on this protein-rich species, likely due to their greater ability to detoxify plant secondary metabolites (Papachristou and Papanastasis 1994;Giger-Reverdin et al 2020). Interestingly, also Molnár et al (2021) reported that swine did not consume R. pseudoacacia. Consequently, the resprouts of this fast-growing alien species can be hardly controlled by pigs, at least in the first season after cutting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their genetic resources are in danger of becoming endangered [ 16 ]. Previous studies on GP have primarily focused on genetic analysis and metabolomics at the genetic level [ 17 ], with less attention paid to systematic conservation studies incorporating the biocultural diversity dimension [ 18 ]. This study attempts to the perspective of the biocultural diversity approach to (1) investigate the traditional rearing and management experiences of GP reared by different ethnic groups such as the Lisu and Bai of Nujiang; and (2) reveal the biocultural significance of GP in local people’s diet, medicine, religion, and rituals, while pointing out the current difficulties faced, and proposing suggestions for future development.…”
Section: Introductionmentioning
confidence: 99%